APLIKASI PENGINGAT SHOLAT DAN PENCARIAN MASJID BERBASIS ANDROID - Teguh Priyo Utomo; Muhamad Iqbal Prasetya; Mohamad Ali Murtadho (Jurnal Sistem Informasi dan Informatika (Simika), 2022)
This application is a mobile application designed with the Unified Modeling Language (UML) designconsisting of use cases, activity diagrams, sequence diagrams, and class diagrams using the waterfall methodin research. This sholat application has a prayer schedule feature, mosque map, added mosque points,information, and this application also has a voice notification feature as a reminder feature when enteringprayer time. So with this application, it is expected to provide convenience and help the community in worship,especially in finding the location of mosques around the user, this application is also able to display mosquesaround the user within a distance of 10 km.